2017
DOI: 10.1021/acs.jafc.7b03544
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Characterization of Dairy Cows Treated with Gossypol by Blood Biochemistry and Body Fluid Untargeted Metabolome Analyses

Abstract: To characterize the metabolic disorders of dairy cows treated with gossypol, 12 dairy cows were assigned to either a control group or a treatment group that was fed 1000 mg of gossypol per kilogram of dry matter feed for 28 days. Milk quality was adversely affected, as both milk protein and lactose levels were significantly decreased in the gossypol-treated group (3.40% vs 3.16%, P = 0.044; 5.15% vs 4.91%, P = 0.027; respectively). Plasma samples revealed increases in alanine aminotransferase (P = 0.092), chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…However, this difference is minuscule and without significant difference. Compared with the reference value, high plasma creatine kinase (CK) activity and lactate dehydrogenase may be associated with pregnancy, which was consistent with a previous study . In general, 21 indexes, such as total bilirubin (TBIL), alanine aminotransferase (ALT), and aspartate aminotransferase (AST), of serum biochemistry of GMO cows were detected and compared with those of nonGMO cows (Table ), which confirmed that the GMO cows were in normal physiological condition.…”
Section: Resultssupporting
confidence: 87%
“…However, this difference is minuscule and without significant difference. Compared with the reference value, high plasma creatine kinase (CK) activity and lactate dehydrogenase may be associated with pregnancy, which was consistent with a previous study . In general, 21 indexes, such as total bilirubin (TBIL), alanine aminotransferase (ALT), and aspartate aminotransferase (AST), of serum biochemistry of GMO cows were detected and compared with those of nonGMO cows (Table ), which confirmed that the GMO cows were in normal physiological condition.…”
Section: Resultssupporting
confidence: 87%
“…Higher volatile fatty acid concentration and milk composition yield were found in the HY group compared to the LY group. Recent studies suggested an important relationship between VFAs and milk components [ 2 , 30 , 31 ]. Specifically, of the three principle VFAs, acetate and butyrate are substrates for oxidation and are precursors of lipids [ 32 , 33 ], moreover propionate is the only glucogenic VFA, accounting for 65–80% of the net glucose supply in lactating dairy cows [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that due to host-microbiota interactions, different cows may harbour different microbial species compositions, which are closely related to distinct differences in rumen fermentation parameters and milk composition. Furthermore, recent findings suggest an important relationship between VFAs and milk components [2, 25, 26]. Specifically, of the three principle VFAs, acetic and butyric acids are substrates for oxidation and are precursors of lipids [27, 28].…”
Section: Discussionmentioning
confidence: 99%